THE ROLE OF ENGLISH AS A GLOBAL LANGUAGE IN INTERNATIONAL COMMUNICATION - Sabrina Abdurahimova Abdullo qizi (TADQIQOTLAR, 2026)
Abstract: The increasing interconnectedness of the modern world has led to the emergence of English as the dominant global language. This paper explores the role of English in facilitating international communication across various domains, including business, education, science, and diplomacy. Based on an analysis of existing scholarly literature, the study examines the historical, political, and economic factors that contributed to the global spread of English. It also evaluates the concept of English as a lingua franca and discusses the advantages and challenges associated with its widespread use. The findings indicate that while English significantly enhances global interaction and access to information, it also raises concerns related to linguistic inequality, cultural dominance, and the marginalization of local languages.